1989
DOI: 10.1111/j.1476-5381.1989.tb11866.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a new potent CCK antagonist, lorglumide, on caerulein‐ and bombesin‐induced pancreatic secretion and growth in the rat

Abstract: 1 The effect of lorglumide, a new potent cholecystokinin (CCK) antagonist, on pancreatic secretion and growth induced by caerulein and bombesin was studied in the rat. 2 Pancreatic exocrine secretion was studied both in vitro (isolated and perfused pancreatic segments) and in vivo (anaesthetized animals with cannulation of the common bile duct) whereas the trophic effect was investiged after short-term (5 days) administration of the peptides and/or lorglumide. 3 Both caerulein and bombesin stimulated amylase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…The mediation of CCK in the ca nine pancreatic secretion induced by bombe sin is also supported by the previous finding that bombesin, unlike CCK, is unable to stimulate amylase release from the dispersed canine pancreatic acini [26], It is of interest that in rats, but not in other species, bombe sin stimulates exocrine pancreas mainly by direct action on acinar cells and not through the release of CCK and gastrin or via cholin ergic pathways. This is supported by obser vations showing that the stimulation of pan creatic protein or enzyme secretion induced by bombesin cannot be suppressed by pep tidergic or nonpeptidergic antagonists of CCK receptors either in vivo or in vitro [ 19,27,28], More detailed studies confirmed the presence of specific and separate receptors for CCK and bombesin-like peptides in the rat pancreas [2].…”
Section: Discussionsupporting
confidence: 51%
“…The mediation of CCK in the ca nine pancreatic secretion induced by bombe sin is also supported by the previous finding that bombesin, unlike CCK, is unable to stimulate amylase release from the dispersed canine pancreatic acini [26], It is of interest that in rats, but not in other species, bombe sin stimulates exocrine pancreas mainly by direct action on acinar cells and not through the release of CCK and gastrin or via cholin ergic pathways. This is supported by obser vations showing that the stimulation of pan creatic protein or enzyme secretion induced by bombesin cannot be suppressed by pep tidergic or nonpeptidergic antagonists of CCK receptors either in vivo or in vitro [ 19,27,28], More detailed studies confirmed the presence of specific and separate receptors for CCK and bombesin-like peptides in the rat pancreas [2].…”
Section: Discussionsupporting
confidence: 51%
“…Both peptides are potent and polyvalent releasers of several gastroin testinal peptides [2,18], some of which may affect exocrine pancreas, CCK being the most important one. However, the lack of effect of lorlumide, a new potent CCKreceptor antagonist [26] and the in vitro effects of bombesin-like peptides on amylase release [11,12,21,29] strongly suggest a direct stimulatory effect of these peptides on exocrine pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…The CCKAR has been reported to be implicated as a mediator of pancreatic growth in response to cholecystokinin and tumorigenesis in the pancreas (Povoski et al 1994;Scarpignato et al 1989). Recently, Takiguchi et al (1997) reported that the OLETF CCKAR gene possesses a homozygous DNA deletion that includes the promoter region and the first and second exons, and therefore can not be expressed in the pancreas.…”
Section: Discussionmentioning
confidence: 97%